The value The Value of Tri Kaya Parisudha Local Wisdom as a Form of Religious Education Transformation - Ni Nyoman Kurnia Wati; I Gede Suwindia (UNHI PRESS, 2022)
This study aims to develop the values ??of local wisdom, especially Tri Kaya Parisudha, in transforming education. The development of the value of local wisdom Tri Kaya Parisudha is due to the increasing loss of local wisdom along with the increasingly rapid development of the times. This type of research is Research and Development (R&D) using a 4D development model. The subjects in this study were two experts or expert practitioners in the field of religion, five internal practitioners at STAHN Mpu Kuturan, and 86 respondents in the limited test. Methods of data collection in this study using interviews, questionnaires, and document studies. The data analysis method used the descriptive qualitative data analysis method. Content validation against indicators of local wisdom values ??was analyzed using Content Validity Ratio (CVR) analysis. Limited test results on the value of local wisdom using the average score of the respondents. Based on the research results at the definition stage, a needs analysis was carried out, namely 1) Performing an analysis of the values ??of Hindu local wisdom. 2) Formulation of local wisdom values ??following the vision and mission of STAH N Mpu Kuturan Singaraja. At the design stage, activities are carried out, including 1. Preparation of indicators for local wisdom values. 2. Preparation of the Tri Kaya Parisudha Questionnaire. Several activities are carried out at the development stage, including a) Content validity test. b) Revised indicators and questionnaires. The product is disseminated through quality assurance (P2M) STAHN Mpu Kuturan Singaraja at the dissemination stage.